(untitled) (Bangladesh Journal of Livestock Research, 2021)
Livestock is generally considered a key asset for rural livelihoods in Bangladesh. After crops, it is the second most significant agriculture-related subsector. In addition, livestock is a means of cash income, nutrition, and a good source of organic fertilizer that boost soil health and fertility. Women’s participation in this sector is remarkable in the last decade superseding the history recorded. Adult women’s involvement in the production of cattle and poultry increased from 43% in 1987 to 51% in 2000 and then to 69% in 2008. They play a pivotal role in livestock management, feeding, processing, and selling as well as acting as a care provider. Though they participated in all steps of livestock rearing, they have very little control over the income earned from livestock production. However, women’s ownership, processing, and consumption of animal and poultry products enhance their capacity for making decisions. These are the essential elements of empowering women politically, socially, and economically; as a result, they offer a means for rural women to escape the cycle of poverty. The current study examined how women participated in the growth of the livestock industry and how they were empowered. Results based on the articles reviewed, almost cent percent of women were the decision maker for rearing livestock. In the overall decision-making process in livestock and poultry rearing 42% of women respondents were followed by 39% of men and 19% of both participated in this regard. Moreover, it is also clear that livestock rearing by women made positive changes in economic, social, and political indicators. This review also summarized some problems and constraints which were faced by the women involved in this sector. According to the discussion, the recommendation would be to encourage women’s participation with utmost effort so that they can overcome challenges and build capacity with confidence in livestock production. Bang. J. Livs. Res. Vol. 28 (1&2), 2021: P. 1-15